BIOEROSION IN THE PLEISTOCENE OF SOUTHERN ITALY: ICHNOGENERA CAULOSTREPSIS AND MAEANDROPOLYDORA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The ichnogenera Caulostrepsis Clarke and Maeandropolydora Voigt are re—examined and redescribed on the basis of new material from Cretaceous deposits at Ivö (Sweden) and in particular from Pleistocene deposits from southern Italy. The morphological differences between the two ichnogenera are explained as having originated by different modes of substrate penetration. Maeandropolydora's gallery is extended from the end of one limb (axial boring), whereas Caulostrepsis's gallery advances at the vertex (lateral boring). Combinations of the two processes give rise to intermediate forms: Caulostrepsis contorta, in which lateral boring prevails and Maeandropolydora decipiens, in which axial boring is predominant. Structures that are U—shaped or produced by elaboration of this basic U—plan (C. contorta) are referred to the ichnogenus Caulostrepsis; the ichnospecies are separated according to presence/absence of vane, pouches, apertural pits and apertural grooves. The different ichnospecies of Maeandropolydora are characterized by presence or absence of pouches or by galleries tending to run in pairs,
Keywords: Trace fossils; Taxonomy; Polychaetes.